ChemInform Abstract: A Comprehensive Study of Soft Magnetic Materials Based on FeSi Spheres and Polymeric Resin Modified by Silica Nanorods. Issue 43 (21st October 2014) - Streckova, M.; Fuzer, J.; Kobera, L.; Brus, J.; Faberova, M.; Bures, R.; Kollar, P.; Lauda, M.; Medvecky, L.; Girman, V.; et al., et al.
Abstract Review: 43 refs.